2018
DOI: 10.1007/s10482-018-1029-5
|View full text |Cite
|
Sign up to set email alerts
|

Formal description of Mycobacterium neglectum sp. nov. and Mycobacterium palauense sp. nov., rapidly growing actinobacteria

Abstract: The taxonomic positions of two fast growing mycobacteria (CECT 8778 and CECT 8779) were established using a polyphasic approach. The strains were shown to have chemotaxonomic, cultural and morphological properties consistent with their classification in the genus Mycobacterium. Multi-locus sequence analyses (MLSA) show that strain CECT 8778 forms a well-supported clade together with the type strains of Mycobacterium aurum, Mycobacterium austroafricanum and Mycobacterium vanbaalenii while strain CECT 8779 prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…Susceptibility to different antibiotics was determined using minimum inhibitory concentration test strips on Mueller-Hinton agar (not the broth method recommended by CLSI). The results showed that the four strains were susceptible to ampicillin, azithromycin, aztreonam, chloramphenicol, erythromycin, fosfomycin, rifampicin, tetracycline and trimethoprim, which is in contrast to the patterns of M. aurum NCTC 10437 T (resistant to rifampicin, troleandomycin and vancomycin), M. austroafricanum CCUG 37667 T (resistant to troleandomycin and vancomycin), M. monacense JCM 15658 T (B9-21-178 T in [33]; variable to trimethoprim-sulfamethoxazole), M. murale JCM 13392 T (resistant to ceftazidime, chloramphenicol and penicillin G) and M. sarraceniae JCM 30395 T (resistant to aztreonam and trimethoprim) [12,[33][34][35].…”
Section: Phenotypic Physiological and Biochemical Analysesmentioning
confidence: 82%
“…Susceptibility to different antibiotics was determined using minimum inhibitory concentration test strips on Mueller-Hinton agar (not the broth method recommended by CLSI). The results showed that the four strains were susceptible to ampicillin, azithromycin, aztreonam, chloramphenicol, erythromycin, fosfomycin, rifampicin, tetracycline and trimethoprim, which is in contrast to the patterns of M. aurum NCTC 10437 T (resistant to rifampicin, troleandomycin and vancomycin), M. austroafricanum CCUG 37667 T (resistant to troleandomycin and vancomycin), M. monacense JCM 15658 T (B9-21-178 T in [33]; variable to trimethoprim-sulfamethoxazole), M. murale JCM 13392 T (resistant to ceftazidime, chloramphenicol and penicillin G) and M. sarraceniae JCM 30395 T (resistant to aztreonam and trimethoprim) [12,[33][34][35].…”
Section: Phenotypic Physiological and Biochemical Analysesmentioning
confidence: 82%
“…The genus Mycobacterium was divided into five genera, including an emended genus Mycobacterium , and four novel genera, namely, Mycolicibacterium gen. nov., Mycolicibacter gen. nov., Mycolicibacillus gen. nov., and Mycobacteroides gen. nov. by Gupta et al ( 2018 ) on the basis of phylogenomic and comparative genomic studies of 150 out of 188 type strains. Moreover, there were other novel species belonging to the genus Mycobacterium being published (Nouioui et al, 2018 ) at the same time. Therefore, the taxonomic statuses of more than 38 species belonging to the emended genus Mycobacterium must be confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…3 The bacteriological analysis of healthy goats in this study revealed that goats could harbor a variety of zoonotic pathogens in their intestines during their growth, especially in the pre-weaning stage. These zoonotic bacteria mainly include the previous reported Lactococcus garvieae, 8 Helicobacter pylori, 8,9 Klebsiella pneumoniae, 10 Shigella sonnei, 11 Shigella boydii, 12 Campylobacter coli, 13 Salmonella enterica, 14 Acinetobacter baumannii, 15 Shigella flexneri, 12 Shigella dysenteriae, 12 Clostridium perfringens, 16 Campylobacter jejuni, 13 Campylobacter lanienae, 17 Salmonella bongori, 18 Campylobacter fetus, 19,20 Listeria monocytogenes, 21 Acinetobacter haemolyticus, 22 Mycobacterium tuberculosis, 23 Mycobacterium neglectum, 24 and Burkholderia pseudomallei. 25 The results suggest that goats may act as a reservoir for many zoonotic bacteria.…”
Section: Discussionmentioning
confidence: 99%